Oligarchie: wymienianie, wyliczanie, obliczanie - Derrida, Jacques (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The following text is the first chapter of Jacques Derrida’s book Politiques de l’amitié [The Politics of Friendship], being the exemplary and standard case of deconstruction, in this particular case, of philosophical texts (Cicero, Plato and, notably, Aristotle). The starting point for the discussion is the performative contradiction inscribed in the wellknown fragment On friendship from Essays by Michel de Montaigne: “O mes amis, il n’y a nul amy” (O my friends, there is no friend). Apparently, everything here is well-known and obvious, even the very notion of friendship, but as we proceed in the argument provided by Derrida, the obvious becomes less obvious to us and takes on new shades and hues in meaning, acquires new values. What is objective mixes in this fascinating argument with what is subjective. What is friendship? What is friendship today? Is friendship limited to just private sphere of interpersonal relations? The answer to the latter question is, according to Derrida, clearly negative. In the course of his argument he states: “There is no democracy without a community of friends”. This argument provides clues to understand a particular archeology of the notion, revealing oblique senses and contexts of the word “friendship”, its istory shown from the antiquity to the present day.